Gastrointestinal involvement in adult IgA vasculitis (Henoch-Schönlein purpura): updated picture from a French multicentre and retrospective series of 260 cases. (24th March 2020) - Audemard-Verger, Alexandra; Pillebout, Evangéline; Amoura, Zahir; Cacoub, Patrice; Jourde-Chiche, Noémie; Lioger, Bertrand; Martis, Nihal; Moulis, Guillaume; Rivière, Etienne; Baldolli, Aurélie; Girard, Charlotte; Goutte, Julie; et al.
Abstract: Objectives: To describe the clinical presentation, treatments and prognosis of gastrointestinal (GI) involvement in adult IgA vasculitis (IgAV). Methods: Data from 260 adults with IgAV included in a French multicentre retrospective survey were analysed. Presentation and outcomes of patients with (GI+) and without (GI-) GI involvement were compared. Results: One hundred and thirty-seven (53%) patients had GI involvement. Initial manifestations were abdominal pain in 99%, intestinal bleeding in 31%, diarrhoea in 26% and acute surgical abdomen in only 4%. Abdominal imaging revealed thickening of intestinal wall in 61%, and endoscopies revealed abnormalities in 87%, mostly mucosal ulcerations. GI+ vs GI- patients were younger (46 ± 18 vs 54 ± 18 years; P = 0.0004), had more constitutional symptoms (43% vs 23%; P = 0.0005) and joint involvement (72 vs 50%; P = 0.0002), and higher CRP levels (3.7 vs 1.9 mg/dl; P = 0.001). Clinical response and relapse rates were comparable between groups, and all causes mortality (2 vs 4%) and IgAV-related mortality (1% vs 2%) as well. GI-related deaths were due to intestinal perforation and mesenteric ischaemia. Conclusion: GI involvement is frequent in adult IgAV. GI involvement is frequent in adult IgAV. Mortality is not uncommon but does not seem to be specifically related to GI. Immunosuppressants should not be preferred as first-line therapy for GI+ patients but may be required in case of acute surgical abdomen.